The presidency of Ulysses S. Grant - Calhoun, Charles W. 1948- (American presidency series, 2017)
"As controversial in politics as he was in the military, Ulysses S. Grant (1822-1885) was an embattled president, enormously popular with the American people, yet the target of unrelenting censure by political enemies. For the first time in almost a century, this book by the distinguished historian Charles W. Calhoun examines Grant's administration in depth, offering a fresh look at the 18th president's policies and actions during his two terms in office (1869-1877). Most biographers focus on Grant's military career, giving less attention to the significant and complex questions that marked his presidential terms. These concerns, the issues of politics and governance, are at the core of this book.